The Silent Revolution: A Holistic Strategy To Address Prehypertension In Young And Active Populations - Yunus, Moch.; Supriyadi, Supriyadi; Wahjuni, Endang Sri (Jurnal Health Sains, 2025)
Prehypertension is an increasingly prevalent condition among young individuals, particularly those who are physically active. Although not as severe as hypertension, prehypertension can elevate the risk of future cardiovascular diseases. Therefore, it is crucial to implement a holistic approach that integrates exercise, stress management, and dietary changes to manage prehypertension effectively. This study aims to analyze the effectiveness of a holistic approach in addressing prehypertension among young populations through a Systematic Literature Review (SLR). The research methodology follows the PRISMA guidelines by analyzing 32 accredited and relevant international publications. The analysis results indicate that regular physical activity, such as aerobic exercise and High-Intensity Interval Training (HIIT), can significantly reduce blood pressure. Additionally, stress management techniques like meditation, yoga, and progressive relaxation have also proven effective in lowering blood pressure. Dietary modifications, including reduced sodium intake, increased potassium consumption, and adherence to healthy eating patterns, contribute positively to managing prehypertension. In conclusion, a holistic approach that combines exercise, stress management, and healthy eating can serve as an effective strategy for preventing and managing prehypertension in young individuals.